Effect of Reviews, Content, and Price on Purchasing Decisions in Islamic Business - Danisa Rahmi Ramadina; Suhendar Suhendar; Heni Verawati (Penerbit Goodwood, 2026)
Purpose: The purpose of this study was to examine the effect of Product Reviews, marketing content, and TikTok Shop price perceptions on purchasing decisions for Facetology Sunscreen by Gen Z in Bandar Lampung, viewed from Islamic businesses. Methodology/approach: This research employs a quantitative methodology. 2,228 members of Generation Z in Bandar Lampung made up the study's population. Sampling strategy: This study employs non-probability sampling strategies and the Slovin formula to obtain up to 96 consumer samples of Facetology Triple Care Sunscreen in Bandar Lampung. Results/findings: Based on research on Gen Z in Bandar Lampung, product reviews, marketing content and price perception significantly and positively influence the purchase decision of Facetology Triple Care Sunscreen. In the perspective of Islamic business, the purchase decision must also consider the halal aspects of the product, the way it is obtained, and the good intentions for the welfare of the Ummah. Conclusion: The main conclusion is that Product Reviews, Marketing content, and price perception positively and significantly drive the purchase decision of Facetology Triple Care Sunscreen in Generation Z in Bandar Lampung. Limitations: A limitation of the study is that it focused only on Generation Z in Bandar Lampung and did not examine the direct influence of Islamic business considerations on their purchasing decisions. Contribution: The contribution of this study is to provide empirical evidence on the influence of Product Reviews, marketing content, and price perceptions on Gen Z sunscreen purchase decisions in Bandar Lampung, complemented by the perspective of Islamic Business Ethics.